Peripheral inflammatory biomarkers and risk factors of dementia in the Chilean GERO cohort: Developing topics. (7th December 2020) - Orellana, Paulina; Duran‐Aniotz, Claudia; Baez, Pablo; Gomez, Rodrigo; Lillo, Patricia; Villagra, Roque; Thumala, Daniela; Toledo, Carolina; Cabello, Victoria; Henriquez, Fernando; Parrao, Teresa; Gonzalez, Christian; et al.
Abstract: Background: Dementia is one of the mean causes of disability in elderly. Peripheral inflammatory biomarkers and ApoE‐ε4 allele have been described as important biological risk factors of dementia in Caucasian population. Currently, there is scarce information about the specific age‐related and predisposition factors to develop dementia in Latino populations. The aim of this study is to investigate these biological risks factors in Chilean elderly with healthy and pathological brain ageing. Method: We evaluated and quantified plasma samples obtained from the GERO cohort (114 elderly subjects, >70 years, classified in 51 subjects with subjective cognitive complaint (SCC) and 63 with mild cognitive impairment (MCI)), in addition to 36 healthy brain controls (HBC) and 31 subjects with Alzheimer's disease dementia (ADD). Genotyping of ApoE gene was analyzed by qPCR. We analyzed inflammatory biomarkers using Luminex technique including IL‐2, IL‐6, IL‐10, TNF‐α, CRP and SAP proteins. All subjects receive a clinical and neuropsychological assessment. Result: CRP protein was found significant decrease expression in SCC and ADD groups compared to MCI and HBC (p=0.048). In SAP protein was found a significant decrease in expression in the SSC (p=0.04) and MCI (p=0.0178) groups compared to HBC. It was observed a positive correlation in the SCC, MCI and ADD groups with the IL‐6 and TNFα, and, SAP and CRP. A negative correlation between IL‐2, IL‐6 and IL‐10 cytokines was found with Direct Span Digit test, which assess attentional capacity. Also was identified a negative correlation between SAP protein and the Free and Cued Selective Reminding Test (FCSRT), which assess verbal episodic memory, and IL‐10 cytokine and Montreal Cognitive Assessment (MoCA), which assess global cognition. Finally, a positive correlation was found in CRP protein with Pfeffer Functional Activity Questionnaire. Frequency of the ApoE‐ε4 allele, was significantly higher in ADD (52%) and SCC (27%) patients than controls and MCI (p=1x10 ‐4 ). Conclusion: The results shown correlations between the different inflammatory proteins and performance in neuropsychological test suggesting that inflammatory biomarkers are associated with pathological brain ageing. The correlations in SCC and MCI are not being reported previously. Additionally, the frequency of ApoE‐ε4 allele in ADD group is higher than worldwide populations.